KOMPETENSI KEPRIBADIAN KEPALA SEKOLAH - Desilia Rachma Sari; Manap Somantri (Manajer Pendididikan, 2019)
This research described the principal personality competence in Senior High School 1 Ketahun. This research was designed with qualitative descriptive method. Subject of this research was the head master of  Senior High School 1 Ketahun. The data were collected by interviews, observations and documentation. Then the collected data analyzed with qualitative technique. The results of this study identifies that (1) the headmaster of Senior High School 1 Ketahun has the integrity of personality as a leader through the ability to find the right, the attitude of responsibility, cultivate trust, appointment, care, honest and consistent. (2) the principal has a desire in self-development through an understanding of the importance of life goals, initiative, loving ideas and experimenting, daring to innovate, optimistic and daring to learn a thing. (3) the principal has an open attitude in implementing the basic tasks and functions through its ability to deliver messages objectively, be content-oriented, and seek information. (4) the ability of the principal to control himself through his ability to regulate implementation, control the stimulus and be able to anticipate events. (5) the principal has the talent and interest in the position shown through his understanding of the principal's position. Finally, based on the results of the discussion above, the researcher suggests to the principal to more develop the indicator of self development especially in simple attitude and ethic while act.